The dragon pack snack attack - Tanis, Joel E. (New York : Four Wind Press, 1993)
After spending hundreds of years on a tropical island, a patrol of bored and hungry dragond invades civilization and indulges in a fanatic fast food binge.
Keywords: Dragons-Fiction; Food Habits - Fiction